FEATURES COMPENSATED ASYNCHRONOUS MACHINES WITH A DIFFERENT NUMBER OF THEIR PHASES - Makarevich, S.; Chuenko, R. (Energy and Automation, 2016)
Compensated m - phase (with m = 2k + 1≥3) and single-phase (m = 1) are similar in phase stator windings. Under the scheme rotary autotransformer (AT) from the capacitance at the output were made. The physical processes capacitance induction machines, energy efficiency and special terms of the principle of reversibility were detected.